(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
This article aims to discuss the limits of the competence oversighting of CNJ, especially with regard to political acts practiced by the judiciary, such as the initiative of bills of matters reserved to a particular organ of power.